SAT0191 Patterns of interstitial lung disease in rheumatoid arthritis and abatacept. multicenter study of 63 patients. (15th June 2017) - Fernández-Díaz, C; Castañeda, S; Ojeda, C; Olivé, A; Carreira, P; Perez-Sandoval, T; Retuerto, M; Cervantes, E; Rodriguez, S; Robles, B; Hernandez, B; Urruticoechea, A; et al.
Abstract : Background: Disease modifying antirheumatic drugs (DMARDs) such as methotrexate (MTX), leflunomide (LFN) or antiTNFα have been implicated in development/exacerbation of Interstitial lung disease (ILD)of rheumatoid arthritis (RA). Several radiological patterns of ILD have been described: i) usual interstitial pneumonia (UIP), ii) nonspecific interstitial pneumonia (NSIP), iii) obliterating bronchitis (OB), and iv) Organized pneumonia (OP) Objectives: To assess the response to Abatacept (ABA) in these patterns of ILD Methods: Multicenter study of RA-ILD treated with ABA. ILD was diagnosed by high-resolution CT scan (HRCT) and classified in radiological patterns (Travis et al). We consider 3 subgroups: a) UIP, b) NSIP and c) "other" (OB, OP or mixed). ABA was used at iv or sc standard dose. We assessed: a) Dyspnea (Medical Research Council-modified scale; significant variations≥1); B) Respiratory function tests; significant changes≥10% in forced vital capacity (FVC) and DLCO≤10%, c) HRCT, d) DAS28. A comparative study was performed for the quantitative (U-Mann-Whitney) and qualitative variables (Fisher test) between the baseline and 3, 6 and 12 months. Results: We included 63 patients (27 women/36 men), mean age; 63.1±9.6 years. At ABA onset the RA had a median evolution of 6.8 [2–13.6] years and the ILD of 1 [0.3–3.03]. RA was seropositive in 85.7%. The diagnosis of ILD was confirmed by biopsy (n=18). The ILD was related to DMARDs: MTX (4), etanercept (3), adalimumab (3), certolizumab (2), Infliximab (1). ABA was used in monotherapy (26) or combined with other DMARDs (37); LFN (15), Cyclosporin (1), sulfasalazine (4), MTX (6), hydroxychloroquine (10), azathioprine (4), chloroquine (1). Table 1 shows the evolution in the available cases. A significant improvement in dyspnea and HRCT was observed in the NIU type. DLCO remained stable in most patients regardless of the radiological pattern. The activity of RA (DAS28) also improved. Conclusions: ABA appears to be effective in ILD associated-RA, including the pattern of poor prognosis (UIP). References: Travis WD et al. J Respir Crit Care Med 2013 188:733–748. Disclosure of Interest: None declared